Baby Check and the Avon infant mortality study. Issue 9 (September 1991) - Cole, T J; Gilbert, R E; Fleming, P J; Morley, C J; Rudd, P T; Berry, P J
Abstract : Thirty seven sudden, unexpected infant deaths from the Avon study were scored retrospectively for serious illness using a modified version of Baby Check. Three cases (8%) scored very highly. In a small proportion of sudden deaths, Baby Check could have identified serious illness before death and led to hospital admission.